PELATIHAN ANALISIS DATA KATEGORI DALAM MENINGKATKAN PENGETAHUAN DAN KETERAMPILAN ANALISIS DATA BIDANG KESEHATAN - Indawati, Rachmah; Arief Wibowo; Assaye Girma Mengistu; Antonius Yansen Suryadarma5; Surma Elisa Manihuruk (Politeknik Negeri Sriwijaya, 2024)
In health sector, a lot of data is found categorical data. The advantage of this category data can do an 'assessment', 'association' and 'effect' of few variables. On the one hand, students do not explore using categorical data, yet understand comprehensively between one method and another statistical method and only focus on one particular method. The purpose is to conduct training to provide knowledge about the concept data and skills data analysis. The target audience is health students. In order for participants to have interest and the training process is fun, the method used is to provide practice from basic to advanced levels and are given repeatedly according to different cases. The results showed increase in participants knowledge about the concept 72.5% and skills data analysis 78.05%. Evaluation of process and instructor showed good. Giving repeated with different levels of ability can develop sensitivity to health issues and practice data analyze quickly and accurately. So, meaningful soft skill element that can be developed, namely being critical. The systematic material is create fun learning process, generate interest and want to learn. It can build cognitive abilities. Discussions help participants gain knowledge and develop soft skills, namely being able to communicate.